Loss of circadian clock accelerates aging in neurodegeneration-prone mutants - Natraj Krishnan; Kuntol Rakshit; Eileen S. Chow; Jill S. Wentzell; Doris Kretzschmar; Jadwiga M. Giebultowicz (Neurobiology of Disease, 2012)
Circadian clocks generate rhythms in molecular, cellular, physiological, and behavioral processes. Recent studies suggest that disruption of the clock mechanism accelerates organismal senescence and age-related pathologies in mammals. Impaired circadian rhythms are observed in many neurological diseases; however, it is not clear whether loss of rhythms is the cause or result of neurodegeneration, or both. To address this important question, we examined the effects of circadian disruption in Drosophila melanogaster mutants that display clock-unrelated neurodegenerative phenotypes. We combined a null mutation in the clock gene period (per01) that abolishes circadian rhythms, with a hypomorphic mutation in the carbonyl reductase gene sniffer (sni1), which displays oxidative stress induced neurodegeneration. We report that disruption of circadian rhythms in sni1 mutants significantly reduces their lifespan compared to single mutants. Shortened lifespan in double mutants was coupled with accelerated neuronal degeneration evidenced by vacuolization in the adult brain. In addition, per01 sni1 flies showed drastically impaired vertical mobility and increased accumulation of carbonylated proteins compared to age-matched single mutant flies. Loss of per function does not affect sni mRNA expression, suggesting that these genes act via independent pathways producing additive effects. Finally, we show that per01 mutation accelerates the onset of brain pathologies when combined with neurodegeneration-prone mutation in another gene, swiss cheese (sws1), which does not operate through the oxidative stress pathway. Taken together, our data suggest that the period gene may be causally involved in neuroprotective pathways in aging Drosophila.